Quality of Life in Cardiac Surgery: A Concept Analysis (International Journal of Nursing Education, 2020)
The concept of quality of life has been widely used in various fields, especially health and nursing. Theconcept of quality of life in cardiac surgery patients requires a specific definition. Various experts havedefined the concept quality of life. However until now there has not been an agreement on appropriateand specific definitions. The aim to present a concept analysis of quality of life from the perspective ofcardiac surgery. The method used in this paper was the approach of Walker & Avant (2011). This conceptanalysis was carried out with the aid of literature on quality of life obtained through the internet databasesof CINAHL, Proquest, and Google Scholar. The key words of interest were “Quality of Life” and “CardiacSurgery.” The search timeline was adjusted to articles published within 1976 to 2019. This concept analysiswas performed using the 8-step method Proposed by Walker and Avant. This method is identification of theattributes, antecedents and consequences of quality of life led to an operational definition of the concept ofquality of life as the individual’s perception of himself subjectively related to physical, psychological andsocial behavior to be prosperous in his life. This concept analysis was able to show that, quality of life is theindividual’s perception of himself subjectively related to physical, psychological and social behavior to beprosperous in his life. Quality of life will provide benefits to cardiac surgery patients: reduce length of stayand maintenance costs, prevent complications and social isolation